The Post-Issue Performance of Rights Issues in Malaysia - Noraini, Azlan (2009)
This study focuses on the performance of rights issues in Malaysia from December 1999 to 2008. This study finds that after the announcement of rights issues, positive abnormal returns are observed using both CAR and BHAR approaches. However, the results are not significant. This finding is contradictory from findings in US and UK where underperformance is observed after rights issues. This study also demonstrates that the companies prefer to issues rights when the share price is increasing.